Lattice Vibration and Raman Scattering in Anisotropic Black Phosphorus Crystals. Issue 6 (19th April 2018) - Mao, Nannan; Zhang, Shuqing; Wu, Juanxia; Zhang, Jin; Tong, Lianming
Abstract: Here, an overview of recent advances on the Raman spectroscopic studies of 2D black phosphorus (BP) crystals is provided, covering the fundamentals of Raman scattering such as the crystal symmetry and the assignment of the phonon modes, the Raman selection rule that can be used to determine the crystalline orientation, the interlayer coupling that gives rise to the interlayer shear and breathing modes, and the effects of perturbation such as temperature, strain, and pressure. Due to the low in‐plane symmetry of BP, particular attention is given to the anisotropic electron–photon and electron–phonon interactions in BP, which have strikingly distinct characteristics compared with other isotropic 2D materials. The abnormal polarized Raman scattering of anisotropic BP crystals and its dependence on the excitation energy, thickness, and phonon modes are discussed from the viewpoints of the complex Raman tensors and the optical birefringence effect. Furthermore, the calibration of the Raman selection rule in anisotropic BP crystals is discussed, and the versatility of Raman spectroscopy in characterizing the structure of BP, such as the layer number, the type of edges, and the crystalline orientation are considered. Abstract : The recent advances in Raman scattering of black phosphorus (BP) are reviewed, covering the basic concept of crystal symmetry, phonon dispersion, and modes assignment, and the versatility of Raman spectroscopy in charactering the layer number, crystalline orientation, interlayer coupling, edges, and the effects of perturbations. The Raman selection rule of BP with anisotropic electron–photon interactions and electron–phonon interactions is highlighted.